2001
DOI: 10.1083/jcb.153.2.283
|View full text |Cite
|
Sign up to set email alerts
|

Identities of Sequestered Proteins in Aggregates from Cells with Induced Polyglutamine Expression

Abstract: Proteins with expanded polyglutamine (polyQ) tracts have been linked to neurodegenerative diseases. One common characteristic of expanded-polyQ expression is the formation of intracellular aggregates (IAs). IAs purified from polyQ-expressing cells were dissociated and studied by protein blot assay and mass spectrometry to determine the identity, condition, and relative level of several proteins sequestered within aggregates. Most of the sequestered proteins comigrated with bands from control extracts, indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
150
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(154 citation statements)
references
References 52 publications
3
150
1
Order By: Relevance
“…The isolation of recombinant polyglutamine aggregates as fibrillar structures formed in cultured cells has been reported (34)(35)(36). Those studies used methods focused on the isolation of inclusion bodies by using detergent insolubility and the strong fluorescence of GFP tags.…”
Section: Discussionmentioning
confidence: 99%
“…The isolation of recombinant polyglutamine aggregates as fibrillar structures formed in cultured cells has been reported (34)(35)(36). Those studies used methods focused on the isolation of inclusion bodies by using detergent insolubility and the strong fluorescence of GFP tags.…”
Section: Discussionmentioning
confidence: 99%
“…Aggregates, often exposing 'sticky' hydrophobic residues can potentially sequester essential cellular factors leading to cellular toxicity and numerous protein conformational disorders, such as Alzheimer's disease, Parkinson's disease, amyotrophic lateral sclerosis, Huntington's disease and prion diseases (Bucciantini et al, 2002;Olzscha et al, 2011;Suhr et al, 2001). To circumvent the unproductive folding of nascent chains and to prevent misfolding and aggregation of proteins, cells inherently protect their proteome through protein quality control at various stages from protein synthesis to folding and degradation of irreversibly misfolded species.…”
Section: Ii4 Proteostasismentioning
confidence: 99%
“…Toxicity can be due to the exposure of normally buried moieties such as hydrophobic side chains or free main chain NH and CO groups that can lead to non-native hydrogen bond interactions with other proteins (Mossuto et al, 2010). Indeed, several studies have shown that sequestration of metastable and essential cellular factors such as proteins involved in chromatin remodeling, transcription, translation, nuclear import and cytoskeletal structure by the aggregates is the major cause of observed toxicity in vivo (Bucciantini et al, 2002;Chai et al, 2002;Olzscha et al, 2011;Suhr et al, 2001). Aggregates can also interfere with the cellular defense mechanisms by altering protein folding homeostasis (Gidalevitz et al, 2006;Satyal et al, 2000), by blocking proteasome mediated degradation (Bence et al, 2001;Bennett et al, 2005) or by inhibiting autophagy .…”
Section: Prion Protein Extracellularmentioning
confidence: 99%
“…Arrows indicate some of the many stained neuropil inclusions. C, Western blot analysis of the mutant htt-containing and polyubiquitin-containing aggregated material present in the P3 fraction of the purification procedure and in its sucrose fractionation, from the cortex of either a control subject ( C) or from a grademutant exon 1 htt (to allow separation in a cell sorter) and/or CsCl gradient fractionation (Scherzinger et al, 1999;Suhr et al, 2001;Hazeki et al, 2002;Mitsui et al, 2002). Studies on transfected cells very often do not reflect the situation in the tissue of an HD patient mainly because of the massive overexpression achieved by transfection.…”
Section: Discussionmentioning
confidence: 99%